ChemInform Abstract: Cs3ScCl6. Issue 38 (10th September 2014) - Ward, Matthew D.; Ibers, James A.
Abstract Purple blocks of the title compound are obtained as a side product from the reaction of U, SnCl2, Sc, and S in a CsCl flux (evacuated silica tube, 1073 K, 96 h).